Development of an IoT-Based Smart Building Prototype with Installation Component Management Features - Jauzi, Muhamad Fais Halim (Departemen Teknik Elektro dan Informatika Sekolah Vokasi UGM, 2025)
The industrial revolution has brought significant changes in energy consumption patterns, shifting from biomass to fossil fuels, which in turn triggered a surge in greenhouse gas emissions and contributed to climate change. In the era of Industry 4.0, technologies such as the Internet of Things and Augmented Reality have emerged as solutions for creating more efficient and safer systems. This research develops a smart building prototype based on the integration of Internet of Things and Augmented Reality to enhance energy efficiency and safety in electrical installation management. The system uses an ESP32 microcontroller with HTTP protocol to read data from three types of sensors, namely the MQ2 gas sensor, a five-channel flame sensor, and the PZEM-004T sensor for measuring voltage, current, and power comprehensively. All data are transmitted to a Firestore-based server and visualized in real time through a web dashboard built with React and hosted on the Vercel platform. The Augmented Reality feature is developed using AR.js to display electrical wiring diagrams and components such as Miniature Circuit Breakers directly on the electrical panel via mobile devices such as smartphones or tablets. Technicians simply scan the panel to view passive interactive visualizations, including zoom and rotation features, allowing them to understand the installation layout without physically opening the panel. The system is also equipped with an early warning mechanism and automatic activation features such as buzzers and water pumps in the event of fire detection. Additionally, the component management features facilitate the documentation of maintenance history, including component replacements, technical specifications, and visual records, making it easier for technicians to perform maintenance and system audits. The implementation results show that the system successfully integrates Internet of Things, Augmented Reality, and web technologies, offering a potential solution for smart buildings that are efficient, safe, and well-integrated.